Raising African Voices in the Global Dialogue on Care-Leaving and Emerging Adulthood. Issue 1 (February 2020) - van Breda, Adrian Du Plessis; Pinkerton, John
Globalization of knowledge and scholarship raises the challenges of dialogue between Global North and South. Northern knowledge and voice remain privileged, while writing from the South often goes unread. This is true also in emerging adulthood and care-leaving scholarship. The special issue of Emerging Adulthood titled "Care-Leaving in Africa" is the first collection of essays on care-leaving by African scholars. It presents both care-leaving and emerging adulthood scholars from the Global North a unique opportunity to consider the implications of a rising African voice for global dialogue. This article, coauthored by scholars from North and South, argues in favor of North–South dialogue but highlights several challenges inherent in this, including the indigenizing and thus marginalizing of African experience and scholarship and divergent constructions of key social concepts. The authors argue the need for mutually respectful discourse between North and South and present specific recommendations for fostering such global dialogue.